Bioinspired Synthesis of ZnO@polydopamine/Au for Label-Free Photoelectrochemical Immunoassay of Amyloid-β Protein - He, Guangli; Zhou, Yue; Li, Mifang; Guo, Yanzhen; Yin, Hang; Yang, Baocheng; Zhang, Shouren; Liu, Yibiao (Frontiers in Bioengineering and Biotechnology, 2021)
Amyloid-β protein (Aβ) is an important biomarker and plays a key role in the early stage of Alzheimer’s disease. Here, an ultrasensitive photoelectrochemical (PEC) sensor based on ZnO@polydopamine/Au nanocomposites was constructed for quantitative detection of Aβ. In this sensing system, the ZnO nanorod array decorated with PDA films and gold nanoparticles (Au NPs) have excellent visible-light activity. The PDA film was used as a sensitizer for charge separation, and it also was used for antibody binding. Moreover, Au NPs were loaded on the surface of PDA film by in-situ deposition, which further improved the charge transfer efficiency and the PEC activity in visible light due to the localized surface plasmon resonance (LSPR) effect of Au NPs. Therefore, ZnO@polydopamine/Au nanocomposites, significantly enhanced photocurrent response was obtained on this photoelectrode, which provides a good and reliable signal for early detection of Alzheimer's disease. Under the optimized conditions, the PEC immunosensor displayed a wide linear range from 1 pg/mL to 100 ng/mL and a low detection limit of 0.26 pg/mL. In addition, this PEC immunosensor also presented good selectivity, stability, and reproducibility. This work may provide a promising point-of-care testing method toward advanced PEC immunoassays for AD biomarkers.